HUBUNGAN DUKUNGAN KELUARGA DENGAN KONSEP DIRI PASIEN STROKE DI RUMAH SAKIT SANTA ELISABETH MEDAN - Pomarida Simbolon (Poltekkes Kemenkes Jakarta III, 2017)
Stroke is a symptom that occurs due to impaired blood circulation in the brain. Stroke diseases has the third death sequence in the world after heart disease and cancer. Good family support is needed in improving self-concept for stroke patients. This research which aims to determine the relationship of family support with self-concept in patients with stroke in Santa Elisabeth Hospital Medan. The design used in research was analytic survey design using the “cross-sectional” with a sample of 34 respondents and the sampling technique is purposive sampling. The data were collected by questionnaires and held in April 2016. Data analysis using chi-square test with significance level of 5%. Results of the study revealed that good family support (55,9%) and negative self-concept (65,6%). The result of statistical test family support with self-concept value p=0,004 (p<0,05) It means there was significant relationship the family support with self-concept in stroke patients in Santa Elisabeth Hospital Medan. It was expected to nurses improve service to patients, motivate and assistsick family members and nurses work with the famiies in maintaining self concept patients. As for the family was expected to pay attention to patients health condition, motivate sick family members by giving motivation to recover, and assisting the patient in the process of healing.